Life-Based Therapy (LBT): Applying a New Approach to Positive Psychology and Psychotherapy - Ramazan Hassanzadeh (Journal of Modern Psychology)
Objective: The present study aims to propose Life-Based Therapy as a novel approach within the fields of positive psychology and psychotherapy. Life-Based Therapy, also known as Life Therapy, is a therapeutic method that addresses core issues related to one's Life. It emphasizes a deeper understanding of existence, passion for life, hope for the future, and overall longevity. The goal is to enhance well-being, effectiveness, and personal value by focusing on key life elements such as motivation, interest, desire, tension, fulfillment, attachment, love, passion, and well-being.Methods: This study employs a descriptive and exploratory research design. The statistical population consists of theories, techniques, studies, and research conducted in the fields of psychotherapy and counseling. Life-Based Therapy was formulated and refined based on the author's extensive professional, academic, and consultative experience, incorporating relevant theories and existing research within the domain.Findings: Life Therapy provides a framework for understanding the complexities and challenges of life. It encourages individuals to view each moment as an opportunity for existence, growth, and self-realization. By forming a comprehensive picture of a client's life and its multiple domains, the therapist can help the client avoid inefficiencies and wasted time. The therapy supports individuals in defining various areas of life and actively working toward meaningful goals in each of those areas.Conclusion: Life-Based Therapy offers an innovative and structured approach to psychotherapy, focused on enhancing awareness and consciousness of life. It empowers individuals to adapt to life's challenges in a constructive and efficient manner. This method promotes purposeful living and aligns therapeutic intervention with the broader aim of achieving balance, passion, and fulfillment in all aspects of life.